Increasing the Sensitivity of Protections in Electrical Networks up to 1 kV by Using Microprocessor and Semiconductor Release Tripping Devices - A. Yu. Kapustsinski; S. V. Kаnstantsinava (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper deals with the problem of increasing the efficiency of the functioning of electric networks up to 1 kV, namely, the possibility of increasing the sensitivity of protections in networks up to 1 kV, which helps to reduce the protection response currents and, accordingly, reduce the cross-section of cable and wire products. The topicality of this problem is shown and the research tasks are defined. Much attention is paid to the concept of selectivity; attention is also paid to the concepts of full and partial selectivity. “Which protective devices can be considered selective?” is a question that is considered and worked out in sufficient depth in the paper. The negative phenomena that occur when ensuring the selectivity of protections in networks up to 1 kV are systematized and described in detail. Based on a comparative analysis of the parameters of circuit breakers with release tripping devices of various types, a solution to this problem is proposed by using circuit breakers with microprocessor and semiconductor release tripping devices. Additional advantages of microprocessor-based circuit breakers are considered and indicated, as well as their disadvantages are indicated, too. The main expected positive effects from the use of circuit breakers with microprocessor release tripping devices are listed, taking into account the fact that this type of circuit breakers is considered as a complex of devices replaced by it. The article can be recommended to employees of electric power specialties working with networks up to 1 kV.